Is viscoelastic coagulation monitoring with ROTEM or TEG validated?. (17th August 2016) - Solomon, Cristina; Asmis, Lars M.; Spahn, Donat R.
Abstract: Recent years have seen increasing worldwide interest in the use of viscoelastic coagulation monitoring tests, performed using devices such as ROTEM and TEG. The use of such tests to guide haemostatic therapy may help reduce transfusion of allogeneic blood products in bleeding patients and is supported in European guidelines for managing trauma and severe perioperative bleeding. In addition, viscoelastic tests form the basis of numerous published treatment algorithms. However, some publications have stated that viscoelastic tests are not validated. A specific definition of the term validation is lacking and regulatory requirements of the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) have been fulfilled by ROTEM and TEG assays. Viscoelastic tests have been used in pivotal clinical trials, and they are approved for use in most of the world's countries. Provided that locally approved indications are adhered to, the regulatory framework for clinicians to use viscoelastic tests in routine clinical practice is in place.